Motivasi Siswa dalam Menghafal Al-Qur`An Menggunakan Metode Wahdah di Rumah Tahfidz Tuo Surau Jorong Ladang Tibarau Nagari Koto Tangah Kec. Tilatang Kamang - Resti Kurnia Sari; Fauzan Fauzan; Alimir Alimir; Eka Rizal (Reflection : Islamic Education Journal, 2025)
The purpose of this study is to describe and examine the motivation of students at Rumah Tahfidz Tuo Surau Jorong Ladang Tibarau Nagari Koto Tangah District to memorize the Al-Qur’an using the wahdah method. Kamang Tilatang. This study employed a descriptive qualitative methodology, gathering data via documentation, interviews, and observation. The study’s findings demonstrate that two internal and external elements encourage pupils to memorize the Al-Qur’an through the wahdah method. Talent is the primary internal component. Students possess skill in memorizing the Al-Qur’an through the wahdah method because they have a passion for learning letters by heart. A brief correspondence. When employing the wahdah method to memorize the Al-Qur’an, pupils are motivated because of them who declare their desire for Allah SWT’s mercy and intervention. Students at Rumah Tahfidz Tuo Surau possess varying levels of intelligence when it comes to memorization of the Al-Qur’an. The availability of a tahfidz instructor is an external aspect; the teacher stays at the tahfidz home constantly and helps students memorize the Al-Qur’an. When learning the Qur’an, pupils are given certain time to memorize it, allowing them to focus more on the Qur’an memorization process. Factors related to the home environment, such as parents’ genuine support for their children’s adherence to the tahfidz of the Even among students who recite memorization recitations and recitations on memorization, it turns out that many students have not completed the memorization deposit according to what has been determined when it comes to the Koran, even with the right time to memorize and having targeted memorization.